Funding allocation to surgery in low and middle-income countries: a retrospective analysis of contributions from the USA - Gutnik, Lily (BMJ Open, 2015)
OBJECTIVE: The funds available for global surgical delivery, capacity building and research are unknown and presumed to be low. Meanwhile, conditions amenable to surgery are estimated to account for nearly 30% of the global burden of disease. We describe funds given to these efforts from the USA, the world's largest donor nation. DESIGN: Retrospective database review. US Agency for International Development (USAID), National Institute of Health (NIH), Foundation Center and registered US charitable organisations were searched for financial data on any organisation giving exclusively to surgical care in low and middle income countries (LMICs). For USAID, NIH and Foundation Center all available data for all years were included. The five recent years of financial data per charitable organisation were included. All nominal dollars were adjusted for inflation by converting to 2014 US dollars. SETTING: USA. PARTICIPANTS: USAID, NIH, Foundation Center, Charitable Organisations. PRIMARY AND SECONDARY OUTCOME MEASURES: Cumulative funds appropriated to global surgery. RESULTS: 22 NIH funded projects (totalling $31.3 million) were identified, primarily related to injury and trauma. Six relevant USAID projects were identified—all obstetric fistula care totalling $438 million. A total of $105 million was given to universities and charitable organisations by US foundations for 12 different surgical specialties. 95 US charitable organisations representing 14 specialties totalled revenue of $2.67 billion and expenditure of $2.5 billion. CONCLUSIONS AND RELEVANCE: Current funding flows to surgical care in LMICs are poorly understood. US funding predominantly comes from private charitable organisations, is often narrowly focused and does not always reflect local needs or support capacity building. Improving surgical care, and embedding it within national health systems in LMICs, will likely require greater financial investment. Tracking funds targeting surgery helps to quantify and clarify current investments and funding gaps, ensures resources materialise from promises and promotes transparency within global health financing.